Moralitas dalam Eksposisi Kejadian 2:18-24: Implikasinya bagi LGBT di Masyarakat Masa Kini: Morality in the Exposition of Genesis 2:18–24: Its Implications for LGBT Issues in Contemporary Society - Ester Agustini Tandana (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2024)
Love is a central tenet of Christian ethics when it comes to moral absolutes. Indeed, what happens in our efforts to practice morals shows up in our reflections on the nature of morals as well. We are vulnerable to the temptation to reduce the biblical understanding of the rich moral meaning to its